2015
DOI: 10.1152/japplphysiol.01077.2014
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and forced exercise differentially alters the gut microbiome in C57BL/6J mice

Abstract: We have previously shown that voluntary wheel running (VWR) attenuates, whereas forced treadmill running (FTR) exacerbates, intestinal inflammation and clinical outcomes in a mouse model of colitis. As the gut microbiome is implicated in colitis, we hypothesized that VWR and FTR would differentially affect the gut microbiome. Mice (9-10/treatment) were randomly assigned to VWR, FTR, or sedentary home cage control (SED) for 6 wk. VWR were given running wheel access, whereas FTR ran on a treadmill for 40 min/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(230 citation statements)
references
References 49 publications
13
214
2
1
Order By: Relevance
“…In contrast, Bifidobacteriales was slightly, but significantly reduced by the wheel running (p < 0.01). Recently, several studies have reported the effects of exercise on the gut microbiota in humans 11) and in animal models 4) . Thus, it can be seen that voluntary exercise partially, but significantly induces changes in the gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Bifidobacteriales was slightly, but significantly reduced by the wheel running (p < 0.01). Recently, several studies have reported the effects of exercise on the gut microbiota in humans 11) and in animal models 4) . Thus, it can be seen that voluntary exercise partially, but significantly induces changes in the gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent studies investigating the effects of physical exercise in experimental animal models have shown that it might induce changes in the gut microbiota [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using both humans and rodent models have shown that exercise influences both cecal and fecal species richness and modulates bacterial phyla genera that are strongly associated with gastrointestinal immune function and leanness (1,11,36); however, the mechanisms are not fully understood. Our unweighted PCoA plot indicates that differing levels of intrinsic aerobic fitness results in changes in cecal beta-diversity, which is consistent with previous studies in ovarectomized and exer- cised HCR and LCR rats (13,31).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome and its influence on host behaviour, intestinal barrier and immune function are believed to be a critical aspect of the brain-gut axis [47]. While the influence of the gut microbiome on exercise non-response is currently untested in humans, recent evidence in murine models shows that there is a strong correlation between physical and emotional stress during exercise and changes in gastrointestinal microbiota composition [48]. This is an exciting field, ripe with opportunities for investigating the influence of the gut microbiome on the exercise non-response.…”
Section: Other Factors To Consider When Evaluating Exercise Non-responsementioning
confidence: 99%